Urologic Complication of Laparoscopic Appendectomy - DeFoor, Robert (Society of Laparoendoscopic Surgeons, 2001)
Abscess formation after a ruptured appendix is a well-known phenomenon. Extra-abdominal complications are somewhat rare. Here we present an unusual urologic complication in a case of a perforated appendix and abdominal sepsis.